Geochemistry of Ordovician black shales at Meductic, southern Miramichi Highlands, New Brunswick - Hennessy, James; Mossman, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
The geochemistry of black shales is useful for identifying geological events such as anoxia, for predicting the proximity of submarine hydrothermal springs and associated mineral deposits, and for indicating the existence of mineral deposits in precursor terrains. In the Miramichi Highlands of New Brunswick, large massive sulfide deposits occur in a mid-Ordovician (Llanvirnian) sequence of fclsic volcanic and sedimentary rocks of the Tetagouche Group, disconformably overlying relatively monotonous quartzosc wacke and grey-green shale of the Miramichi Group. Black shales commonly occur at the boundary between the Miramichi and Tetagouche groups, and in some areas such as at Meductic in the southern Miramichi Highlands, they display high heavy metal values in common with Scandinavian-Caledonide black shales. Like the massive sulphide deposits, the Meductic metalliferous black shales were deposited in a back-arc basin associated with an island-arc system formed during the closing of the proto-Atlantic Ocean and the onset of the Taconian orogeny. The average Meductic black shale, as deduced from the Bright Eye Brook Formation at the base of the Tetagouche Group, shows high values of V and Ba, moderate enrichment in Nb, Th, Pb, Ti, and Crf and depletion in Sr, Cu and Ni compared to black shale USGS standard SDO-1. Total organic carbon is well above the minimum value for a carbonaceous shale, the highest value (2.35%) corresponding to highest V (3016 ppm) and highest Ba (16,173 ppm). CaO, Fe203 and MnO contents are low, and Si02, K2O and P2O5 contents are relatively high compared to the standard. Chondrite-normalized REE patterns show elevated LREE, fairly flat HREE signatures, a negative Eu anomaly and a slightly positive Cc anomaly. These features are characteristic of marine volcanological dctrital input rather than a hydrothermal regime. Correlation of high V with Ba indicates that conditions were favourable for deposition of both metals. It is postulated that early deposition in an oxic environment (higher than normal MnO) was succeeded by gradual stagnation (increasing levels of V). Concomitant enrichment in Ba under anoxic conditions was linked to a regime of elevated heat flow. This scenario is compatible with the record of sea level fluctuations during the early Palaeozoic.